A Systematic Literature Review on Online Medical Services in Malaysia - Khan, Nohman; Qureshi, Muhammad Imran (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The aim of the study reviews online medical services in Malaysia. The paper reviews the improvement in Malaysian Medical services in the past five years. In this paper, we systematically reviewed literature from the year 2014 to 2018. We selected the web of science database for the literature search to make the process more transparent and clearer, every process is recorded on the excel sheets and all studies were screened through rigorous inclusion and exclusion criteria. Final 48 papers were selected for this systematic literature review and all irrelevant papers are excluded from the study. For the selection and exclusion process, PRISMA 2009 is used. The results revealed that Literature is heavily focusing on the medical services towards the urban areas, but rural areas were largely neglected. Many studies are discussing the importance of online medical services; However, implementation mechanisms have not been discussed. The systematic review recommends that future research should be focused more on holistic patterns of implementations of the online medical services in Malaysia.